The Physician's assistant : an approach to improved patient care - Metropolitan Washington Regional Medical Program (1970)
The Washington Hospital Center proposed to expand its cardiovascular technician program into a physician's assistant program and sent a proposal for funding to the Metropolitan Washington Regional Medical Program. The proposal raised many questions about the proper role of the physician's assistant. The purpose of this report prepared in 1970 by the Metropolitan Washington Regional Medical Program was "to clarify the issue and to make recommendations about how the application for financial support can be revised." The report provides background on the status of 30 physician assistant programs in 1970, provides role descriptions and detailed information about each program investigated by the study.